2016
DOI: 10.1002/tox.22279
|View full text |Cite
|
Sign up to set email alerts
|

Aged garlic extract ameliorates immunotoxicity, hematotoxicity and impaired burn-healing in malathion- and carbaryl-treated male albino rats

Abstract: Malathion and carbaryl are the most widely used organophosphate and carbamate insecticides, respectively, especially in developing countries; they pose a potential health hazard for both humans and animals. Here, we evaluated the protective effects of an odorless (free from allicin) Kyolic aged garlic extract (AGE, containing 0.1% S-allylcysteine; 200 mg/kg body weight) on the toxicity induced by 0.1 LD of malathion (89.5 mg/kg body weight) and/or carbaryl (33.9 mg/kg body weight) in male Wistar rats. Doses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Our laboratory, preliminary experiments indicated that the body weight decreased in the DEN‐treated mice, which potentially related to the appetite loss resulted from the elevation of serum TNF‐α. In addition, the excessive DNA fragmentation and apoptosis shown in the hepatocytes of DEN‐treated mice were probably due to the excessive production of TNF‐α, especially in the presence of GSH depletion, where TNF‐α triggers the extrinsic pathway of apoptosis through its type 1 receptor on the hepatocytes leading to caspase‐8 activation . The activated caspase‐8 transmits a signal bifurcated into two pathways: (a) a direct activation of caspase‐3 (an indicator for completion of the last stage of apoptosis) and (b) an indirect activation of caspase‐3 through triggering the mitochondria‐mediated caspase cascade including caspase‐9 (the intrinsic pathway).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our laboratory, preliminary experiments indicated that the body weight decreased in the DEN‐treated mice, which potentially related to the appetite loss resulted from the elevation of serum TNF‐α. In addition, the excessive DNA fragmentation and apoptosis shown in the hepatocytes of DEN‐treated mice were probably due to the excessive production of TNF‐α, especially in the presence of GSH depletion, where TNF‐α triggers the extrinsic pathway of apoptosis through its type 1 receptor on the hepatocytes leading to caspase‐8 activation . The activated caspase‐8 transmits a signal bifurcated into two pathways: (a) a direct activation of caspase‐3 (an indicator for completion of the last stage of apoptosis) and (b) an indirect activation of caspase‐3 through triggering the mitochondria‐mediated caspase cascade including caspase‐9 (the intrinsic pathway).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the excessive DNA fragmentation and apoptosis shown in the hepatocytes of DEN-treated mice were probably due to the excessive production of TNF-α, especially in the presence of GSH depletion, 35,36 where TNF-α triggers the extrinsic pathway of apoptosis through its type 1 receptor on the hepatocytes leading to caspase-8 activation. 37,38 The activated caspase-8 transmits a signal bifurcated into two pathways 37 : (a) a direct activation of caspase-3 (an indicator for…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organophosphate (OP) compounds are toxic agents that are widely used in agriculture and also in household environments for pest and insect control. In this way, accidental or intentional poisoning by the improper handling of these toxic agents leads to health problems, mainly related to the high inhibition of cholinesterases in the central and peripheral nervous systems …”
Section: Introductionmentioning
confidence: 99%
“…In this way, accidental or intentional poisoning by the improper handling of these toxic agents leads to health problems, mainly related to the high inhibition of cholinesterases in the central and peripheral nervous systems. 1,2 Malathion, [S-1,2(bis-ethoxycarbonyl)ethyl-O,O-dimethyl phosphorodithioate], is an OP that is easily purchased at the local market and widely used as a pesticide in agriculture, residential gardening, public recreation areas, and in public health pest control programmes. 3,4 Due to uncontrolled use, people may be constantly exposed to this compound.…”
Section: Introductionmentioning
confidence: 99%